Combined non-targeted and targeted metabolomics reveals the mechanism of delaying aging of Ginseng fibrous root - Yang, Xiang; Yang, Xiang; Li, Bo; Zhang, Jianyun; Yan, Zhuyun (Frontiers in Pharmacology, 2024)
Background: The fibrous root of ginseng (GFR) is the dried thin branch root or whisker root of Ginseng (Panax ginseng C. A. Mey). It is known for its properties such as tonifying qi, producing body fluid, and quenching thirst. Clinically, it is used to treat conditions such as cough, hemoptysis, thirst, stomach deficiency, and vomiting. While GFR and Ginseng share similar metabolites, they differ in their metabolites ratios and efficacy. Furthermore, the specific role of GFR in protecting the body remains unclear. Methods: We employed ultra-high performance liquid chromatography-triple quadrupole mass spectrometry to examine alterations in brain neurotransmitters and elucidate the impact of GFR on the central nervous system. Additionally, we analyzed the serum and brain metabolic profiles of rats using ultra-high performance liquid chromatography-quadrupole-orbitrap mass spectrometry to discern the effect and underlying mechanism of GFR in delaying aging in naturally aged rats. Results: The findings of the serum biochemical indicators indicate that the intervention of GFR can enhance cardiovascular, oxidative stress, and energy metabolism related indicators in naturally aging rats. Research on brain neurotransmitters suggests that GFR can augment physiological functions such as learning and memory, while also inhibiting central nervous system excitation to a certain degree by maintaining the equilibrium of central neurotransmitters in aged individuals. Twenty-four abnormal metabolites in serum and seventeen abnormal metabolites in brain could be used as potential biomarkers and were involved in multiple metabolic pathways. Among them, in the brain metabolic pathways, alanine, aspartate and glutamate metabolism, arginine and proline metabolism, histidine metabolism, and tyrosine metabolism were closely related to central neurotransmitters. Butanoate metabolism improves energy supply for life activities in the aging body. Cysteine and methionine metabolism contributes to the production of glutathione and taurine and played an antioxidant role. In serum, the regulation of glycerophospholipid metabolism pathway and proline metabolism demonstrated the antioxidant capacity of GFR decoction. Conclution: In summary, GFR plays a role in delaying aging by regulating central neurotransmitters, cardiovascular function, oxidative stress, energy metabolism, and other aspects of the aging body, which lays a foundation for the application of GFR.